2011
DOI: 10.1111/j.1749-7345.2011.00480.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Variations of Ectoparasites on Cage‐reared Channel Catfish, Ictalurus punctatus, in Tamaulipas, Mexico

Abstract: Studies in cage‐cultured fish have reported spatial and temporal variations on parasite prevalence; however, most of these studies have been carried out in cold water and marine environments. Channel catfish, Ictalurus punctatus, is the main floating cages‐raised species used in intensive fish culture in Tamaulipas. In Mexico, there are no seasonal reports on fish parasites in this type of cage system. The aim of the present study was to determine the prevalence and mean intensity of ectoparasites of cage‐cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…However, monogeneans were detected during each sampling throughout the study period which is in accordance with previous studies that reported presence of monogeneans throughout all seasons (Rabago-Castro et al 2011;Jerônimo et al 2011).…”
Section: Discussionsupporting
confidence: 80%
“…However, monogeneans were detected during each sampling throughout the study period which is in accordance with previous studies that reported presence of monogeneans throughout all seasons (Rabago-Castro et al 2011;Jerônimo et al 2011).…”
Section: Discussionsupporting
confidence: 80%
“…It is an important cultured fish species in Mexico (Lara-Rivera et al, 2015), susceptible to bacterial or parasite diseases (Rábago-Castro et al, 2011) endemic to this area; this has increased the use of chemicals on water bodies as treatment against these pathogens, which in turn can result in water contamination. This has led to the quest to find alternatives to enhance fish resistance to disease, and at the same time, to decrease the use of watercontaminating chemotherapeutants.…”
Section: Introductionmentioning
confidence: 99%
“…(2010), S. guanduensis showed higher prevalence and intensity in spring, confirming the expected pattern of infestation by monogeneans in the warmer months (Eiras, 1994). However, the peak abundance of monogeneans in autumn has been observed for some species: Diplectanum piscinarius , a parasite of Plagioscion squamosissimus in the Volta Grande Reservoir, Minas Gerais, Brazil (Martins et al ., 2000); Ligictaluridus floridanus , a parasite of Ictalurus punctatus in Mexico (Rábago-Castro et al ., 2011); Gyrodactylus salaris , a parasite of the Atlantic salmon ( Salmo salar ) (Appleby & Mo, 1997) and Arctic charr (Salvelinus alpinus ) (Winger et al , 2008), both in Norway. According to Jansen & Bakke (1991), seasonal fluctuations in the population of monogeneans can be attributed to changes in the immune response of the hosts and in the water temperature.…”
Section: Discussionmentioning
confidence: 99%